Las fuentes termominerales en Costa Rica I - Von Frantzius, Alexander (Universidad de Costa Rica, 2007)
The following information was published in 1862 in its essential parts, but by mistake in a journal of medical sciences (Prussian Journal of Medicine 1862, N ° 14-16), which has such limited distribution that I've never had this number in sight. Given that the content of such information may be of great interest to researchers and naturalists, is that I hope that the publication of articles in this journal can reach the group which was originally intended.